Heterosexual HIV transmission and STD prevalence: predictions of a theoretical model. Issue 5 (October 1998) - Renton, A M; Whitaker, L; Riddlesdell, M
Abstract : BACKGROUND: Previous studies suggest that concurrent sexually transmitted infection may enhance HIV transmission. This paper explores some theoretical consequences of this using a mathematical model of transmission of HIV and other STD pathogens. OBJECTIVES: To develop a deterministic mathematical model to describe the heterosexual transmission dynamics of both HIV and a bacterial STD. STUDY DESIGN: We used survey derived estimates of sexual behaviour in a young heterosexual London population in our deterministic mathematical model to estimate the effects on an HIV epidemic of different levels of STD prevalence in such a population. RESULTS: We show that the predictions of the model are plausible and suggest that, even under conditions both of low STD prevalence and of low HIV transmission enhancement, a substantial proportion of HIV transmission events may be attributable to concurrent STD. CONCLUSIONS: It is likely that epidemics of heterosexually transmitted HIV infection in industrialised countries have been limited in size by the relative success of efforts to control STD. None the less, a significant proportion of heterosexual transmission events which do occur may be attributable to concurrent STD. In developing countries, cheap and simple STD care is likely to be a highly cost effective strategy to prevent HIV transmission.